Efficacy of Bacteria in Cancer Immunotherapy: Special Emphasis on the Potential of Mycobacterial Species - Podder, Santosh; Rakshit, Srabanti; Ponnusamy, Manikandan; Nandi, Dipankar (Clinical Cancer Drugs, 2016)
Background: Conventional cancer therapies such as chemotherapy and radiotherapy are often characterised by lack of tumor specificity, increased resistance of tumors to drugs, failure to detect metastases and undesirable side effects. Several years back, William Coley’s pioneering work on the use of bacteria opened up the new field of cancer immunotherapy. The search for alternative and better strategies in cancer treatment is an ongoing process. Methods: Articles related to the therapeutic efficacies of different bacterial species against cancer were searched in different scientific journals and databases. This review summarizes the studies on the expediency of different bacterial species in cancer treatment particularly the potential therapeutic efficiency of Mycobacteria. Results: A strain of Mycobacterium bovis, i.e. Bacillus Calmette Guerin, is approved for the treatment of bladder carcinoma. Also, treatment with Mycobacterium vaccae improves the quality of life of patients suffering from some tumors. Recent studies have revealed the efficacy of Mycobacterium indicus pranii in inducing a Th1 priming environment and reducing the in vivo tumor growth in several animal models. Conclusions: The immunotherapeutic potential of different mycobacterial species warrant clinical investigations for a wide range of tumors and may open up a new dimension in cancer therapy. Further studies and technological innovations are likely to shed new light on host responses to tumors, provide a promising regimen of cancer therapeutics and improve the quality of life of cancer patients.
Keywords: immune response